Answer:
A. The solutions are
.
B. The factored form of the quadratic expression ![x^2+9=(x-3i)(x+3i)](https://tex.z-dn.net/?f=x%5E2%2B9%3D%28x-3i%29%28x%2B3i%29)
Step-by-step explanation:
A. To find the solutions to the quadratic equation
you must:
![\mathrm{Subtract\:}9\mathrm{\:from\:both\:sides}\\\\x^2+9-9=0-9\\\\\mathrm{Simplify}\\\\x^2=-9\\\\\mathrm{For\:}x^2=f\left(a\right)\mathrm{\:the\:solutions\:are\:}x=\sqrt{f\left(a\right)},\:\:-\sqrt{f\left(a\right)}\\\\x=\sqrt{-9},\:x=-\sqrt{-9}](https://tex.z-dn.net/?f=%5Cmathrm%7BSubtract%5C%3A%7D9%5Cmathrm%7B%5C%3Afrom%5C%3Aboth%5C%3Asides%7D%5C%5C%5C%5Cx%5E2%2B9-9%3D0-9%5C%5C%5C%5C%5Cmathrm%7BSimplify%7D%5C%5C%5C%5Cx%5E2%3D-9%5C%5C%5C%5C%5Cmathrm%7BFor%5C%3A%7Dx%5E2%3Df%5Cleft%28a%5Cright%29%5Cmathrm%7B%5C%3Athe%5C%3Asolutions%5C%3Aare%5C%3A%7Dx%3D%5Csqrt%7Bf%5Cleft%28a%5Cright%29%7D%2C%5C%3A%5C%3A-%5Csqrt%7Bf%5Cleft%28a%5Cright%29%7D%5C%5C%5C%5Cx%3D%5Csqrt%7B-9%7D%2C%5C%3Ax%3D-%5Csqrt%7B-9%7D)
![x=\sqrt{-9} = \sqrt{-1}\sqrt{9}=\sqrt{9}i=3i\\\\x=-\sqrt{-9}=-\sqrt{-1}\sqrt{9}=-\sqrt{9}i=-3i](https://tex.z-dn.net/?f=x%3D%5Csqrt%7B-9%7D%20%3D%20%5Csqrt%7B-1%7D%5Csqrt%7B9%7D%3D%5Csqrt%7B9%7Di%3D3i%5C%5C%5C%5Cx%3D-%5Csqrt%7B-9%7D%3D-%5Csqrt%7B-1%7D%5Csqrt%7B9%7D%3D-%5Csqrt%7B9%7Di%3D-3i)
The solutions are:
![x=3i,\:x=-3i](https://tex.z-dn.net/?f=x%3D3i%2C%5C%3Ax%3D-3i)
B. Two expressions are equivalent to each other if they represent the same value no matter which values we choose for the variables.
To factor
:
First, multiply the constant in the polynomial by
where
is equal to -1.
![x^2+9i^2](https://tex.z-dn.net/?f=x%5E2%2B9i%5E2)
Since both terms are perfect squares, factor using the difference of squares formula
![a^2-i^2=(a+i)(a-i)](https://tex.z-dn.net/?f=a%5E2-i%5E2%3D%28a%2Bi%29%28a-i%29)
![x^2+9=x^2+9i^2=\left(-3i+x\right)\left(3i+x\right)](https://tex.z-dn.net/?f=x%5E2%2B9%3Dx%5E2%2B9i%5E2%3D%5Cleft%28-3i%2Bx%5Cright%29%5Cleft%283i%2Bx%5Cright%29)
Answer 400
Step-by-step explanation: 1 hours = 60 min
60 min divided by 9 = 6.66666667
6.66666667 * 5 dozen pretzels/ 60 pretzel = 400
did it pretty quickly may be wrong
A = 15 a = athena, s = samantha, b = bonus points
s = b + a
s = b + 15
Answer:
A
Step-by-step explanation:
He borrowed money so he has -5 dollars and but he payed 2 back, so now he needs to pay $3